2014
DOI: 10.1007/s00223-014-9935-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Bone MicroRNome in Osteoporotic Fractures

Abstract: Osteoporosis causes important morbidity among elderly individuals. Fragility fractures, and especially hip fractures, have a particularly negative impact on the patients' quality of life. The role of epigenetic mechanisms in the pathogenesis of many disorders is increasingly recognized, yet little is known about their role in non-malignant bone disorders such as osteoporosis. The aim of this study was to explore the expression of miRNAs in patients with osteoporotic hip fractures. Trabecular bone samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 33 publications
2
44
0
1
Order By: Relevance
“…This underlines the need to validate, in individual samples, the results of the profiling stage. In another study, Garmilla-Ezquerra et al [22], describe a differential expression of 13 miRNAs (nominal P \ 0.05) in primary osteoblasts from BF patients and osteoarthritic controls, as in the present study. Although they try to replicate the miR-210 (nominal P = 0.06), because it seems to have been associated with osteoblast activity in human bone samples in a recent study [23], no statistical significance arises at the validation stage.…”
Section: Discussionsupporting
confidence: 57%
“…This underlines the need to validate, in individual samples, the results of the profiling stage. In another study, Garmilla-Ezquerra et al [22], describe a differential expression of 13 miRNAs (nominal P \ 0.05) in primary osteoblasts from BF patients and osteoarthritic controls, as in the present study. Although they try to replicate the miR-210 (nominal P = 0.06), because it seems to have been associated with osteoblast activity in human bone samples in a recent study [23], no statistical significance arises at the validation stage.…”
Section: Discussionsupporting
confidence: 57%
“…A more comprehensive study examined the expression of 760 miRNAs in trabecular bone samples obtained from the femoral heads of patients with osteoporotic hip fractures and showed that 13 miRNAs (let‐7i, miR‐135a, miR‐137, miR‐181a‐2, miR‐187, miR‐193a‐3p, miR‐214, miR‐330‐5p, miR‐518f, miR‐519d, miR‐524, miR‐636, and miR‐643) displayed significant differences: seven with higher levels in bones from osteoporotic patients and the other six in the nonfractured bones. The authors selected six miRNAs (miR‐187, miR‐193a‐3p, miR‐214, miR518f, miR‐636, and miR‐210) for further analysis and found that miR‐187 levels were 5.3‐fold higher in the nonfracture group, whereas miR‐518f levels were 8.6‐fold higher in bones from fractures of osteoporotic patients; the other four did not show any statistical differences between the two groups …”
Section: Mirna Profiling and Fracturesmentioning
confidence: 99%
“…The authors selected six miRNAs (miR-187, miR-193a-3p, miR-214, miR518f, miR-636, and miR-210) for further analysis and found that miR-187 levels were 5.3-fold higher in the nonfracture group, whereas miR-518f levels were 8.6-fold higher in bones from fractures of osteoporotic patients; the other four did not show any statistical differences between the two groups. (31) More recently, screening serum levels of 139 patients, (32) which included controls, osteopenic (with and without fractures), and osteoporotic (with and without fracture), for the presence of circulating miRNAs, found miR122-5p and miR-4516 to be present at significantly different levels between nonosteoporotic control, osteopenic, and osteoporosis patients. Specifically, miR-122-5p levels were much lower in osteoporosis patients compared with nonosteoporotic control and osteopenic patients.…”
Section: Mirna Profiling and Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…177 Yavropoulou et al analyzed circulating miRNAs to identify potential biomarkers for osteoporosis and osteoporotic fractures. 178 Five miRNAs were significantly deregulated in the serum of patients with low bone mass compared with controls, two of which ( miR-29a and miR-2861 ), have already been discussed in this review.…”
Section: Mirnas Associated With Skeletal Disease and Other Orthopaedimentioning
confidence: 99%